2018
DOI: 10.1038/s41598-018-20494-y
|View full text |Cite
|
Sign up to set email alerts
|

Black silicon significantly enhances phosphorus diffusion gettering

Abstract: Black silicon (b-Si) is currently being adopted by several fields of technology, and its potential has already been demonstrated in various applications. We show here that the increased surface area of b-Si, which has generally been considered as a drawback e.g. in applications that require efficient surface passivation, can be used as an advantage: it enhances gettering of deleterious metal impurities. We demonstrate experimentally that interstitial iron concentration in intentionally contaminated silicon waf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
4
16
1
Order By: Relevance
“…Chakraborty et al presented similar results and reported that phosphorus diffusion gettering reduced the concentration of light‐induced defects, which were suspected to be Cu, Ni, and Ti, by nearly one order of magnitude . Interestingly, our previous study demonstrated that heavy phosphorus‐doping in the b‐Si spikes after an industry‐typical POCl 3 diffusion process enhances iron segregation to the emitter, which substantially improves minority carrier lifetime in iron‐contaminated substrates . Consistent with earlier reports, sheet resistance is indeed substantially lower in the b‐Si than in the acidic‐textured cells (~50 Ω/□ vs ~80 Ω/□).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Chakraborty et al presented similar results and reported that phosphorus diffusion gettering reduced the concentration of light‐induced defects, which were suspected to be Cu, Ni, and Ti, by nearly one order of magnitude . Interestingly, our previous study demonstrated that heavy phosphorus‐doping in the b‐Si spikes after an industry‐typical POCl 3 diffusion process enhances iron segregation to the emitter, which substantially improves minority carrier lifetime in iron‐contaminated substrates . Consistent with earlier reports, sheet resistance is indeed substantially lower in the b‐Si than in the acidic‐textured cells (~50 Ω/□ vs ~80 Ω/□).…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, the large surface area of b‐Si is no longer a hindrance for high‐efficiency b‐Si solar cells due to the advancements in novel surface passivation methods . In fact, it has been recently shown that the large surface area can provide also an advantage, since it significantly enhances gettering of deleterious metal impurities during phosphorus diffusion …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black silicon surfaces can be achieved using different techniques that can be easily incorporated in the PV industry such as metal‐assisted wet‐chemical etching (MACE), dry reactive ion etching (RIE), inductive couple plasma–reactive ion etching (ICP‐RIE), laser structuring, and electrochemical etching . Additionally, collateral benefits of b‐Si have arisen recently improving low‐cost substrates by removing saw surface damage in diamond‐wire‐sawn (DWS) wafers or increasing the gettering effect during doping diffusion on Czochralski (CZ) c‐Si solar cells . All these advantages make black silicon etching a very attractive candidate to replace conventional acidic and alkaline texturizing approaches in the PV fabrication chain.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, collateral benefits of b-Si have arisen recently improving low-cost substrates by removing saw surface damage in diamond-wire-sawn (DWS) wafers 5 or increasing the gettering effect during doping diffusion on Czochralski (CZ) c-Si solar cells. 6 All these advantages make black silicon etching a very attractive candidate to replace conventional acidic and alkaline texturizing approaches in the PV fabrication chain. For instance, Modanese et al 7 demonstrated the economic viability of replacing acidic texturing by ICP-RIE b-Si nanostructures using a convectional industrial process on the basis of mc-Si substrates.…”
Section: Introductionmentioning
confidence: 99%